Short- and long-term risk of atrial fibrillation recurrence after first time ablation according to body mass index: a nationwide Danish cohort study. Issue 2 (8th December 2022) - Tønnesen, Jacob; Pallisgaard, Jannik; Ruwald, Martin H; Rasmussen, Peter Vibe; Johannessen, Arne; Hansen, Jim; Worck, Rene Husted; Zörner, Christopher R; Riis-Vestergaard, Lise; Middelfart, Charlotte; Gislason, Gunnar; Hansen, Morten Lock
Abstract: Aims: Overweight is associated with increased risk of atrial fibrillation (AF), but the impact of overweight and AF recurrence after ablation is less clear. Despite this, an increasing number of AF ablations are carried out in overweight patients. We investigated the impact of body mass index (BMI) on AF recurrence rates after ablation. Methods and results: Through Danish nationwide registers, all patients undergoing first-time AF ablation between 2010 and 2018 were identified. Exposure of interest was BMI. The primary outcome was recurrent AF, defined from either any usage of antiarrhythmic medication, AF hospitalization, cardioversion, or re-ablation. A total of 9188 patients were included. Median age and interquartile range was 64 (60–75) in the normal-weight group and 60 (53–66) in the morbidly obese. There was an increase in comorbidity burden with increasing BMI, including a higher prevalence of heart failure, chronic obstructive pulmonary disease, diabetes, and hypertension. At 1- and 5-year follow ups, recurrence rates of AF increased incrementally by BMI categories. The hazard ratios and 95% confidence intervals of recurrent AF after ablation were 1.15 (1.07–1.23), 1.18 (1.09–1.28), and 1.26 (1.13–1.41) in overweight, obese, and morbidly obese, respectively, compared with normal-weight patients. Procedure duration and X-ray dose exposure also increased with increasing BMI. Conclusion: Following AF ablation, recurrence rates of AF increased incrementally with increasing BMI. Therefore, aggressive weight management pre ablation in overweight patients could potentially provide substantial benefits and improve short- and long-term outcomes after ablation. Graphical Abstract: Graphical Abstract